Electrochemical conversion of Ni2(OH)2CO3 into Ni(OH)2 hierarchical nanostructures loaded on a carbon nanotube paper with high electrochemical energy storage performance. Issue 5 (19th December 2014) - Chen, Hongyuan; Kang, Yiran; Cai, Feng; Zeng, Sha; Li, Weiwei; Chen, Minghai; Li, Qingwen
Abstract : Amorphous Ni2 (OH)2 CO3 nanowire arrays on a CNT paper were electrochemically converted into a Ni(OH)2 nanosheet with high capacitance for supercapacitors. Abstract : Large-diameter carbon nanotube (CNT) paper was used as a porous and conductive template to obtain vertically aligned Ni2 (OH)2 CO3 nanowire array shells, which could be further converted into highly active Ni(OH)2 nanosheets by a cyclic voltammetry strategy. The as-prepared hierarchical nanostructure showed superior electrochemical performance for the electrodes of supercapacitors.